The burden of color vision defect in Nepal – an iceberg phenomenon - Khatri, Anadi; K.C, Bal Kumar; Gautam, Sudhir; Kharel, Muna (Journal of Chitwan Medical College, 2019)
Background: Color vision tests are routinely performed and are mandatory in most part of the world. However, in Nepal and many other developing countries, color vision may often be overlooked. We evaluated a possible burden of color vision in a group of patients who were specifically evaluated for a color vision defects. This study evalutes the awareness of color vision defect among the patients evaluated and highlights the importance of the color vision evaluation. Methods: A sequential group of 73 people from August to September 2017 specifically evaluated for color vision defect for recruitment of government employment were evaluated. Ishiharapseudo-isochromatic plates and Farnsworth-Munsell Dichotomous D-15 test were used for screening. Mean and Standard deviation were used for descriptive analysis of the data. Results: Fifty-seven were male and sixteen were female. The mean age was 23 years (SD ± 3.7). On evaluation of the color vision defect, 9 (12.3%) were found to have total color vision defect (achromatopsia), 3 (4%)-red-green defect and 1(1%) with blue red defect. None of the patients had undergone color vision test at eye hospital previously. There were 4 patients who were registered drivers who had color vision defect. Conclusions: Color vision is an important part of the vision. It should not be ignored.All of the patients evaluated were found to be unware of their condition. Early detection of color vision defects in individuals, if possible, at school level can help them to determine their careers and future endeavors at early stage.